PENANAMAN NILAI SOSIAL DALAM MEMBENTUK KARAKTER SISWA MELALUI PEMBELAJARAN IPAS DI SD NEGERI 11 KECAMATAN GUNUNG MEGANG KABUPATEN MUARA ENIM - Pintaria; Middya Boty; Djoko Rohadi Wibowo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the process of instilling social values ​​in shaping students' character through natural and social sciences learning at SDN 11 Gunung Megang District, Muara Enim Regency. The main focus of the study is social values ​​in the form of mutual cooperation, politeness, honesty, and discipline which are considered important in shaping students' character. The research method used is qualitative descriptive with data collection techniques through observation, interviews, and documentation. The results of the study indicate that instilling social values ​​in natural sciences learning is carried out through various strategies such as habituation, giving examples, teacher supervision, and integration of moral values ​​in subject matter. Although there are obstacles such as lack of student awareness and parental involvement, efforts to overcome them are carried out through a personal approach, motivation, and cooperation between school residents. Instilling social values ​​has been proven to play a significant role in shaping students' character, both in the school environment and in society. Therefore, natural sciences learning needs to continue to be developed as an effective vehicle for character education.